From Presenter to Producer: Librarian as Leader of a Departmental Seminar Series. Issue 4 (2nd October 2019) - Brandenburg, Marci D.; Martin, Scott
ABSTRACT: This case study describes the University of Michigan (U-M) Bioinformationist's coordination and leadership of the Department of Computational Medicine & Bioinformatics (DCMB) Tools and Technology Seminar series. Her role includes finding speakers, scheduling speakers, and promotion. The authors conducted an assessment, based on talk attendance, speaker affiliation, and more to determine the primary factors driving attendance. The results of this analysis will inform future semesters. The Bioinformationist's management of this seminar has increased visibility for the library and represents a less explored method for creating a strong partnership with an academic department.